ENVIRONMENTALLY INDUCED MIGRATION IN THE CONTEXT OF THE CORONAVIRUS PANDEMIC - Moiseeva Evgeniya M.; Lukyanets Artem S. (Scientific Journal of Pedagogy and Economics, 2021)
The purpose of this article is to identify the specific trends of migration flows induced by negative environmental changes in the context of the COVID-19 pandemic. First of all, based on an analysis of meteorological data it was proved that in the near future, the risk of dangerous natural disasters that might cause large-scale population movements remains no less high than in the past few years. A temporary reduction in CO2 emissions due to a reduction in industrial production and transportation along with restrictive infection control measures will be short-term and insufficient to slow down climate change. Consequently, we can expect that during the pandemic the number of environmental migrants throughout the world will not decrease and might reach about 20 million people a year only due to forced relocations caused by weather-related hazards. In this study, we use the term environmental migrants to refer to both those people who have been forced to leave their place of residence due to natural or technological disasters, and those people who have voluntarily decided to migrate under amid slow-onset environmental degradation. Both of these categories of migrants are already exposed to the risks posed by adverse environmental conditions. In the context of a coronavirus pandemic, additional risks begin to affect each group differently. Internally displaced people will face problems caused by restrictions on movement imposed in most countries, as well as poor sanitary and hygienic conditions during evacuation and at temporary accommodation centers, which greatly increase the risk of infection and further spread of the virus. Voluntary environmental migrants in most cases move because of the inability to continue their usual economic activities in the changing environmental situation in their home region and the need to find a job in a sphere which does not depend directly on natural and climatic conditions. Most often these are farmers who look for temporary employment in cites. This category of migrants will be adversely affected by the economic consequences of the coronavirus pandemic, namely, the reduction of jobs and wages in a number of industries, especially ones that are related to public services and transportation. A cut in remittances will reduce the adaptive potential of their environmentally vulnerable home areas, and lead to further deterioration of the environment and living conditions of the population